Chinese foreign relations : power and policy since the cold war - Sutter, Robert G. ([S.l.] : Rowman & Littlefield Publishers, 2012)
China is rightly considered an emerging power in world affairs as Chinese leaders, backed by growing economic and military strength, engage in innovative diplomatic approaches that pave the way for China's international role. But this is only part of the story of China$1 (Bs rise. As Robert G. Sutter shows in this meticulous and balanced assessment, the record of twists and turns in Chinese foreign relations since the end of the Cold War highlights a very different perspective. Domestic problems, nationalism, and security concerns continue to preoccupy Beijing, complicating China's influence and innovations in foreign affairs. On the international front, the actions of other powerful nations and growing dependence on the world economy complicate as well as enhance China$1 (Bs advance to international prominence. Newly revised, this edition features more extensive treatment of China$1 (Bs role in the international economy and greater discussion of its relations with the developing world. Providing a comprehensive introduction to Chinese foreign relations, Sutter shows Chinese leaders exerting growing influence in world affairs but remaining far from dominant. Facing numerous contradictions and trade-offs, they move cautiously to avoid major confrontations, costly commitments, or mistakes that could undermine their one-party rule as they deal with an international environment posing numerous challenges as well as opportunities for Chinese interests.s
Keywords: China; International relations; Political science; World politics